Noise reduction method for vibration signals 2D time‐frequency distribution using anisotropic diffusion equation. (7th February 2014) - Yin, Aijun; Zhao, Lei; Yang, Zhengyi; Chen, Benqian
<x xml:space="preserve">Abstract</x> Threshold noise reduction methods of vibration signals have been widely researched and used. However, these methods are less efficient in such situation, including requiring a time‐consuming and subjective to manual editing because different degree of noise signal requires selecting different characterization for filtering. In this paper, an efficient denoising method based on PDE for mechanical vibration signals time‐frequency distribution is investigated, in which, a one‐dimensional vibration signal is transformed into 2D time‐frequency domain by using Gabor transform. This enables (i) simultaneously utilize both time and frequency characteristic for effectively multiple dimension signal denosing and (ii) isotropic and anisotropic characteristics to be imposed by employing PDE, which explicitly fit with the local structure of time‐frequency signal. This paper analyzes the basic methods of isotropic and anisotropic diffusion filtering, investigates the anisotropic diffusion method based on local feature structure of 2D information, and conducts a set of comparative tests. Experiments show that this proposed method has a better performance of denoising than that of thresholding. At the same time, it is more handy than that of other methods, such as independent component analysis. Finally, problems and ways of improving the PDE‐based filter method are analyzed in this paper. Copyright © 2014 John Wiley & Sons, Ltd.